Análise comparativa de programas de habitação social em três municípios no interior do Estado de São Paulo realizados em regime de mutirão: estratégias de atuação dos atores sociais envolvidos - Kageyama, Carloline Vitti (Universidade Federal de São Carlos, 2001)
The issue of housing in Brazil was redefined in the 1990’s within the current context of administrative decentralization and the increase in power at the local level, the widening of participation and the extent to which civil society is organized, and the closing down of state organs and institutions such as the BNH which provided support for social housing projects. Within this context, the number of municipal programs for housing development has increased, particularly in small and medium-sized cities. The hypothesis which guided this research was that the social actors involved in housing programs in the inland municipalities of the state of Sao Paulo (local government officials, organizations of future homeowners, political parties, technical advisors, unions, the community, etc.) exercise differing degrees of influence during each phase of the construction process which are specific to each of the housing developments, thereby reflecting distinct general strategies. To test this research hypothesis, three recent housing programs were chosen (Franca, Jaboticabal and Monte Alto) with the aim of identifying the social actors responsible and their degree of influence for the various phases in the process of the housing development. The method used consisted of a bibliographic review of the literature; the conduction of interviews of the social actors involved in the processes, based on a previously defined set of questions; and the organization and analysis of the data obtained.
Comparative analysis of social housing programs in three municipalities in the interior of the State of São Paulo carried out under a collective effort: action strategies of the social actors involved
Keywords: Habitação social; Mutirão; Programas municipais; Participação popular; Estrategias de atuação; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL